Plan S: An economist's perspective. (20th September 2021) - Armstrong, Mark
Abstract : Many scholarly journals charge high prices to research libraries and generate high profits. Open access regulation, in its various forms, can mitigate this problem. This essay examines one particular policy, "Plan S, " which aims broadly to require regulated authors to publish their research in open access journals, which among other drawbacks of the policy greatly limits their publishing options.